2019
DOI: 10.1002/ajp.22949
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in myelin of axons of the corpus callosum and cognitive decline in common marmosets

Abstract: Executive control is a higher-level cognitive function that involves a range of different processes that are involved in the planning, coordination, execution, and inhibition of responses. Many of the processes associated with executive control, such as response inhibition and mental flexibility, decline with age. Degeneration of white matter architecture is considered to be the one of the key factors underlying cognitive decline associated with aging. Here we investigated how white matter changes of the corpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…8 Evidence also suggests that degeneration of OLs and oligodendrocyte precursor cells (OPCs) increases with aging, and researchers have observed demyelination and significant structural changes in myelin of aged rodents, monkeys, and human brain. 5,9,10 Therefore, studying demyelinating pathogenesis in different CNS disorders may deepen our understanding and create possible therapies for these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…8 Evidence also suggests that degeneration of OLs and oligodendrocyte precursor cells (OPCs) increases with aging, and researchers have observed demyelination and significant structural changes in myelin of aged rodents, monkeys, and human brain. 5,9,10 Therefore, studying demyelinating pathogenesis in different CNS disorders may deepen our understanding and create possible therapies for these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…measurements provide values and trends that are similar to those found with histology 35 (21,27). Nevertheless, it is unclear whether the variance captured by the in vivo 36 measurements in the healthy human brain can be translated to meaningful differences in 37 conduction velocity. 38…”
Section: Introductionmentioning
confidence: 60%
“…Such measurements have been shown 41 to be related to callosal structure (31,32), and are likely to increase with age (33,34). The 42 increase in callosal delay time with age could be related to white matter structure, as it 43 has been shown that during aging the brain tissue structure undergoes changes, with 44 accumulating damage to the white matter (35,36), and a decrease in myelination (37). It 45 is still an open question whether -weighted MRI can be related to age dependent 46 changes in callosal delay time.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple drafts are submitted for revision in stages. These thesis papers have been great starts to papers that can later be submitted for publication with student(s) as a co-author (Childers et al, 2012, 2014, 2016; Phillips et al, 2018;Phillips et al, 2019).…”
Section: Designing Research Procedures For Undergraduate Rasmentioning
confidence: 99%